Influence of Online Reviews and Omnichannel Strategy on Buying Interest with Trust Mediation in Pudaksari Bali - Ni Luh Pudak Sariani; Ni Luh Putu Indiani; Ni Made Wahyuni (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This study aims to examine the influence of online customer reviews and omnichannel strategies on buying interest in Pudaksari skincare products in Bali, with trust acting as a mediating variable. The research is motivated by the decline in Pudaksari’s sales performance in 2025 and the increasing importance of digital information and integrated marketing channels in shaping consumer behavior. A quantitative approach was employed using a survey method involving 110 respondents selected through purposive sampling. Data were collected via an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that online customer reviews have a positive and significant effect on buying interest but do not significantly influence trust. Conversely, omnichannel strategies do not directly affect buying interest, yet they have a positive and significant impact on trust. Trust is found to significantly and positively influence buying interest. Furthermore, trust does not mediate the relationship between online customer reviews and buying interest, but it fully mediates the relationship between omnichannel strategies and buying interest. These findings suggest that strengthening an integrated and consistent omnichannel strategy is more effective in increasing consumer buying interest through building trust, rather than relying solely on online customer reviews. This study contributes to digital marketing literature by highlighting the critical role of trust as a psychological mechanism linking omnichannel integration and consumer buying interest in the local skincare industry.